Role of Virulence Factors of Trypanosomatids in the Insect Vector and Putative Genetic Events Involved in Surface Protein Diversity - de Castro Neto, Artur Leonel; da Silveira, José Franco; Mortara, Renato Arruda (Frontiers in Cellular and Infection Microbiology, 2022)
Trypanosomatids are flagellate protozoans that can infect several invertebrate and vertebrate hosts, including insects and humans. The three most studied species are the human pathogens Trypanosoma brucei, Trypanosoma cruzi and Leishmania spp. which are the causative agents of Human African Trypanosomiasis (HAT), Chagas disease and different clinical forms of leishmaniasis, respectively. These parasites possess complex dixenous life cycles, with zoonotic and anthroponotic stages, and are transmitted by hematophagous insects. To colonize this myriad of hosts, they developed mechanisms, mediated by virulence factors, to infect, propagate and survive in different environments. In insects, surface proteins play roles in parasite attachment and survival in the insect gut, whilst in the mammalian host, the parasites have a whole group of proteins and mechanisms that aid them invading the host cells and evading its immune system components. Many studies have been done on the impact of these molecules in the vertebrate host, however it is also essential to notice the importance of these virulence factors in the insect vector during the parasite life cycle. When inside the insect, the parasites, like in humans, also need to survive defense mechanisms components that can inhibit parasite colonization or survival, e.g., midgut peritrophic membrane barrier, digestive enzymes, evasion of excretion alongside the digested blood meal, anatomic structures and physiological mechanisms of the anterior gut. This protection inside the insect is often implemented by the same group of virulence factors that perform roles of immune evasion in the mammalian host with just a few exceptions, in which a specific protein is expressed specifically for the insect vector form of the parasite. This review aims to discuss the roles of the virulence molecules in the insect vectors, showing the differences and similarities of modes of action of the same group of molecules in insect and humans, exclusive insect molecules and discuss possible genetic events that may have generated this protein diversity.